Legume Breeding for the Agroecological Transition of Global Agri-Food Systems: A European Perspective - Rubiales, Diego; Annicchiarico, Paolo; Vaz Patto, Maria Carlota; Julier, Bernadette (Frontiers in Plant Science, 2021)
Wider and more profitable legume crop cultivation is an indispensable step for the agroecological transition of global agri-food systems but it represents a challenge especially in Europe. Plant breeding is pivotal in this context. Research areas of key interest are represented by innovative phenotypic and genome-based selection procedures for crop yield, tolerance to abiotic and biotic stresses enhanced by the changing climate, intercropping, and emerging crop quality traits. We see outmost priority in the exploration of genomic selection opportunities and limitations, to ease genetic gains and limit the costs of multi-trait selection. Reducing the profitability gap of legumes relative to major cereals will not be possible in Europe without public funding devoted to crop improvement research, pre-breeding and, in various circumstances, public breeding. While most of these activities may profit of significant public-private partnerships, all of them can provide substantial benefits to seed companies. A favourable institutional context may comprise some changes to variety registration tests and procedures.